Intrapartum and neonatal mortality in primary midwife-led and secondary obstetrician-led care in the Amsterdam region of the Netherlands: A retrospective cohort study. Issue 12 (December 2015) - Wiegerinck, M.M.J.; van der Goes, B.Y.; Ravelli, A.C.J.; van der Post, J.A.M.; Klinkert, J.; Brandenbarg, J.; Buist, F.C.D.; Wouters, M.G.A.J.; Tamminga, P.; de Jonge, A.; Mol, B.W.
Abstract: Objective: to compare intrapartum- and neonatal mortality and intervention rates in term women starting labour in primary midwife-led versus secondary obstetrician-led care. Design: retrospective cohort study. Setting: Amsterdam region of the Netherlands. Participants: women with singleton pregnancies who gave birth beyond 37+0 weeks gestation in the years 2005 up to 2008 and lived in the catchment area of the neonatal intensive care units of both academic hospitals in Amsterdam. Women with a primary caesarean section or a pregnancy complicated by antepartum death or major congenital anomalies were excluded. For women in the midwife-led care group, a home or hospital birth could be planned. Measurements: analysis of linked data from the national perinatal register, and hospital- and midwifery record data. We assessed (unadjusted) relative risks with confidence intervals. Main outcome measures were incidences of intrapartum and neonatal (<28 days) mortality. Secondary outcomes included incidences of caesarean section and vaginal instrumental delivery. Findings: 53, 123 women started labour in primary care and 30, 166 women in secondary care. Intrapartum and neonatal mortality rates were 37/53, 123 (0.70‰) in the primary care group and 24/30, 166 (0.80‰) in the secondary care group (relative risk 0.88; 95% CI 0.52–1.46). Women in the primary care group were less likely to deliver by secondary caesarean section (5% versus 16%; RR 0.31; 95% CI 0.30–0.32) or by instrumental delivery (10% versus 13%; RR 0.76; 95% CI 0.73–0.79). Key conclusions: we found a low absolute risk of intrapartum and neonatal mortality, with a comparable risk for women who started labour in primary versus secondary care. The intervention rate was significantly lower in women who started labour in primary care. Implications for practice: these findings suggest that it is possible to identify a group of women at low risk of complications that can start labour in primary care and have low rates of medical interventions whereas perinatal mortality is low. Highlights: We compared term women who started labour in midwifery versus obstetricianled care. A previous comparable study found a higher mortality rate in midwifery-led care. In our study, overall intrapartum and neonatal mortality rates were low and comparable between the groups. Intervention rates were lower in the midwifery led care group.